The Role of Administrative Audit in Reducing Financial and Administrative Corruption: An Exploratory Study on a Sample of Academics in the Accounting Department in a Sample of Public and Private Universities in the Kurdistan Region of Iraq - Ali, Barzan O. (Mitanni Journal of Humanitarian Sciences, 2022)
This study aims to demonstrate the extent of the importance of the role of administrative audit in reducing financial and administrative corruption in institutions from the point of view of a sample of academics in the Accounting Department and in a sample of public and private universities in the Kurdistan Region of Iraq. Financial and administrative, because the success of the administrative auditor in discovering and combating financial and administrative corruption helps protect the economy from the collapses that institutions are exposed to. The descriptive analytical method was relied upon in order to answer the problem of the study. The researcher prepared a questionnaire consisting of (20) questions to answer the research questions, and the data was unloaded and subjected to statistical treatments using the SPSS statistical program. The research sample consists of a group of (48) teaching staff in the accounting department in the universities of the Kurdistan Region of Iraq. One of the most important findings of the research is that the administrative audit is the examination and evaluation of the internal control system and all financial statements, as well as examining the accounting books and records to verify the results of the project work and to ensure the integrity of the financial position of the institution. In light of these results, the researcher presented a set of recommendations, the most important of which is the need to pay attention to examining and evaluating the control and internal audit system on an ongoing basis and correcting its weaknesses by the administration, which could help reduce the existence of an atmosphere of administrative and financial corruption.